Leisure´s culture citadel: the turning point of São Paulo Commerce Social Service (SESC) on 80´s - Dines, Yara Schreiber (2014)
The present work is focused on leisure in São Paulo city, in an attempt to grasp the meanings which this concept and that of culture have come to take on in this metropolitan context during the last decades of the 20th century. The article is centered on an institution designed to provide leisure for workers – the São Paulo Commerce Social Service, SESC – and it analyses the guide lines that have oriented its course of action and the social practices it has been implementing since mid 80´s. The research was based on the iconographic collection of the SESC São Paulo and interviews with members and former workers of the institution, thus allowing for the analysis of the iconography to be sent in proper context. This methodology unvelled the significance of the various practices of sport and culture developed by the institution along its existence, thus permitting us to identify some aspects of the guiding lines followed by the SESC São Paulo, and to reflect upon the meanings taken on by leisure and culture within this universe, in the dialogue it has established with the metropolis.